Application of a system of immune status complex inspection in personnel ofchemical production - T. T. Radzivil; I. V. Oradovskay; V. T. Antipin (Бюллетень сибирской медицины)
Screening examinations of chemical industry workers aimed at early revealing immunodeficiency status, subclinical forms of thyroid gland diseases, oncologic diseases, diseases of a gastrointestinal tract and pathology of mammary glands. Levels of a thyrotrophic hormone (TTH) and of free thyroxin, oncologic organ-specific markers, basic subpopulations of lymphocytes were determined blood serum. The study results revealed basic immune-pathologic syndromes which require immune corrective measures in practically healthy people; subclinical forms of thyroid gland diseases, cancers of various localization. Necessity of introduction the given kinds of studies in periodic medical surveys which are annually performed in enterprises nuclear industry.